The concept of autonomy in Latin America and Brazilian foreign policy - Stipic, Igor; Gotz Betancourt, Shirley; Zajíček, Miroslav, 1975-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
The objective of this thesis is to analyze the concept of autonomy, taking as the case study Brazil under the Workers Party Government (2003-2016). Approach that will be taken aims at combining perspectives of Latin-American structuralism with those of realism and interdependency. Thesis essentially concentrates on two specific issue areas: global economy and international politics. By constructing a theoretical framework, I aspire to identify and analyze various factors considered to have a direct impact on the study matter. In doing so, I consider the behavior of distinct variables and their effect on the degree of autonomy. Finally, thesis addresses problems of international insertion for peripheral countries, considering possibilities and limits of truly autonomous action.
Vedoucí práce: Shirley Gotz Betancourt
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: ekonomická a regionální studia latinské ameriky [obor dipl. práce]; diplomové práce; master's theses